Main morphofunctional alterations of the human urinary tract: an integrative literature review (Research, Society and Development, 2022)
Introduction: the morphological alterations of the urinary tract can be subdivided into four main groups: renal anomalies in terms of shape and position; number and volume renal anomalies; collecting system anomalies and urinary bladder anomalies. Objective: to elucidate the main morphofunctional changes in the human urinary tract. Methodology: this is an integrative literature review. The research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases. Information Services. Results and Discussion: The first group of alterations includes abnormally rotated kidneys, renal ectopia and renal fusion. These alterations, which are relatively frequent, always culminate in inefficient urine drainage, a factor that can determine a secondary ureteric morphological alteration due to the development of hydronephrosis, for example. The second set of changes are less common and more independent than those relating to kidney shape and position. In this sense, the following can be mentioned: supernumerary kidneys, which are usually unilateral and not hereditary; renal hypoplasia; renal agenesis; and cystic disease, which occurs due to a failure in the genesis of the junction that would allow urine to pass from the glomerulus to the renal pelvis. It is worth remembering that, with age, there is a physiological loss of renal tissue, which can make an individual, even if healthy, fit into the group of people with morphological changes in volume. Conclusion: renal anomalies in terms of shape and position, renal anomalies in number and volume, anomalies of the collecting system and anomalies of the urinary bladder must be studied and well understood by professionals, so that it is possible to recognize such changes and understand how to approach them.